Low-temperature growth of well-aligned zinc oxide nanorod arrays on silicon substrate and their photocatalytic application - Azam A (Dove Medical Press, 2014)
Ameer Azam,1 Saeed Salem Babkair21Center of Nanotechnology, King Abdulaziz University, Jeddah, Saudi Arabia; 2Center of Nanotechnology, Department of Physics, Faculty of Science, King Abdulaziz University, Jeddah, Saudi ArabiaAbstract: Well-aligned and single-crystalline zinc oxide (ZnO) nanorod arrays were grown on silicon (Si) substrate using a wet chemical route for the photodegradation of organic dyes. Structural analysis using X-ray diffraction, high-resolution transmission electron microscopy, and selected area electron diffraction confirmed the formation of ZnO nanorods grown preferentially oriented in the (001) direction and with a single phase nature with a wurtzite structure. Field emission scanning electron microscopy and transmission electron microscopy micrographs showed that the length and diameter of the well-aligned rods were about ~350–400 nm and ~80–90 nm, respectively. Raman scattering spectra of ZnO nanorod arrays revealed the characteristic E2 (high) mode that is related to the vibration of oxygen atoms in the wurtzite ZnO. The photodegradation of methylene blue (MB) using ZnO nanorod arrays was performed under ultraviolet light irradiation. The results of photodegradation showed that ZnO nanorod arrays were capable of degrading ~80% of MB within 60 minutes of irradiation, whereas ~92% of degradation was achieved in 120 minutes. Complete degradation of MB was observed after 270 minutes of irradiation time. Owing to enhanced photocatalytic degradation efficiency and low-temperature growth method, prepared ZnO nanorod arrays may open up the possibility for the successful utilization of ZnO nanorod arrays as a future photocatalyst for environmental remediation.Keywords: ZnO, nanorods, XRD, photodegradation